The impact of direct vertebral rotation (DVR) on radiographic outcome in surgical correction of idiopathic scoliosis - Urbanski, Wiktor (Arch Orthop Trauma Surg, 2017)
INTRODUCTION: Recent developments of spinal instruments allow to address nearly all components of idiopathic scoliosis. Direct vertebral rotation (DVR) maneuver was introduced to correct apical axial vertebral rotation. It is however still not well established how efficiently DVR affects results of scoliosis correction. The object of the study was to evaluate en bloc apical vertebral rotation (DVR) and its impact on coronal and sagittal correction of the spine in patients undergoing surgical scoliosis treatment. MATERIALS AND METHODS: Thirty-six consecutive patients who underwent posterior spinal fusion with pedicle screws only constructs for idiopathic scoliosis. Fifteen patients (20 curves) were corrected by rod derotation only and 21 patients (26 curves) had both rod derotation and DVR. Curve measurements were performed on x-rays obtained before and postoperatively—coronal curves, kyphosis (T2–T12, T5–T12). Spine flexibility was assessed on prone bending x-rays. Apical axial rotation was determined on CT scans obtained intraoperatively and postoperatively. Rotation angle (RAsag) was measured according to Aaro and Dahlborn. RESULTS: We observed reduction of RAsag in all patients; however, in DVR group, decrease was greater, by 31.8% comparing to non-DVR group, by 8.6% (p = 0.0003). Mean coronal correction in DVR group was 68.8% and in rod derotation group without DVR 55% (p = 0.002). No significant correlation was found between degree of derotation obtained and coronal correction. In DVR group T2–T12 kyphosis has increased in 28 (65%) patients whereas in non-DVR group in 31 (69%) cases. Mean value of T2–T12 kyphosis growth was 16.7% in DVR and 22.1% in non-DVR group. These differences however did not occur statistically significant. CONCLUSIONS: Direct vertebral rotation (DVR) maneuver reduces significantly apical rotation of the spine, enhances ability of coronal correction, and it does not reduce thoracic kyphosis.